Dualisme Penetapan Itsbat Nikah atas Pernikahan Non-Muslim Pasca Konversi Agama di Pengadilan Agama - Mulyadi; Gusti Muzainah; Amelia Rahmaniah (An-Nafis: Jurnal Ilmiah Keislaman dan Kemasyarakatan, 2026)
This study examines the dualism in the determination of itsbat nikah (marriage legalization) for non-Muslim marriages following religious conversion at Religious Courts in Indonesia. Using normative-juridical research through case study analysis of Decision Number 25/Pdt.P/2023/PA.Mtw at the Muara Teweh Religious Court, this research investigates how judges reconcile the validity of marriages originally conducted under non-Islamic religious traditions when both spouses subsequently convert to Islam simultaneously. The findings reveal that judges apply classical Islamic jurisprudential principles, particularly the ijma of scholars documented in Bidayatul Mujtahid, which affirms that marriages conducted before conversion to Islam remain valid when both partners embrace Islam together, without requiring a new marriage contract. The court's legal reasoning demonstrates harmonization between the provisions of Law Number 1 of 1974 and Article 7 of the Compilation of Islamic Law (KHI), alongside substantive Islamic jurisprudential principles. This research contributes to understanding legal pluralism in Indonesian family law, particularly regarding the intersection of customary religious practices, Islamic jurisprudence, and state administrative requirements. The study recommends clearer regulatory guidelines to address similar cases involving converts (muallaf) and reduce legal uncertainty, thereby ensuring the protection of family rights.